Characterization of three connexin32 genes and their role in inflammation-induced ATP release in the Japanese flounder Paralichthys olivaceus. Issue 106 (November 2020) - Li, Shuo; Wang, Nan; Zhang, Tongtong; Feng, Yu; Wang, Liyan; Sun, Jinsheng
Abstract: Extracellular ATP (eATP) is a potent singling molecule in activation of fish innate immunity while the molecular determinants for eATP release in fish were not completely understood. Connexin32 (Cx32) is a member of gap junction protein family that plays important immunological functions in mammals. However, the immune relevance of Cx32 and its role in ATP release in fish has not been investigated. Here, we identified, characterized three Cx32 isoform genes ( Cx32.2, Cx32.2x and Cx32.7 ) from the Japanese flounder Paralichthys olivaceus, and investigated their role in inflammation-induced ATP release in fish. Expression analysis revealed that even though all the three Cx32 genes are constitutively expressed in all examined Japanese flounder tissues, Cx32.2 and Cx32.2x are dominantly expressed in liver, and Cx32.7 is highly expressed in intestine and head kidney macrophages. In addition, we showed that gene expression of all the three Cx32 isoforms was modulated by cAMP stimulation and inflammatory challenges. Furthermore, we revealed that Cx32 expression was upregulated in TNF-alpha overexpressed Japanese flounder FG-9307 cells. Moreover, overexpression of the three Cx32 isoforms significantly reduced the gene expression level of LPS-induced pro-inflammatory cytokine IL-8 and TNF-alpha, indicating that Cx32 is involved in modulating inflammatory response in fish. Finally, we showed that inflammation-induced ATP release was significantly increased in Cx32-overexpressed Japanese flounder FG-9307 cells, and this increased ATP release could be attenuated by pre-incubation with gap junction protein blocker carbenoxolone. Taken together, we for the first time reported the involvement of Cx32 in fish immunity. Our findings suggested that in addition to Cx43 and pannexin1 channels, Cx32 also plays a role in inflammation-induced ATP release in fish. Highlights: Three Cx32 isoform genes were expressed in Japanese flounder Paralichthys olivaceus. Cx32 expression was modulated by PAMPs challenge and cAMP stimulation. TNF-alpha overexpression up-regulated Cx32 expression. Cx32 down-regulated LPS-induced pro-inflammatory cytokine expression. Cx32 is an immune response gene involved in inflammation-induced ATP release in fish.